The Perspective of Marketing Mix Elements in Health Care Services – A Review: Life Sciences -Diagnostic industry - Sahdev, Dr. Ashish; Sen Gupta, Dr. Sudipta (International Journal of Life Science and Pharma Research, 2023)
The success of healthcare services and diagnostic laboratories depends on their use of the marketing mix.Price optimization, service expansion, better health education, and more funding are also crucial. Clinical decisions depend onlaboratory diagnosis and test results, helping customize medication for a particular patient. Diagnostic labs are considered a "cashcow" for healthcare organizations. Marketing mix has been considered critical in the success of any service organization, and thesame applies to Healthcare too. A modern and valuable marketing tool in healthcare services is the marketing mix. Patientsatisfaction has been the goal of any healthcare organization’s marketing activity, which is significantly influenced by the 7Ps of theservice marketing mix. Hospitals have been using the 7Ps of the marketing mix for a long time, and a lot of literature is available.At the same time, the literature on the applicability of marketing mix tools in the diagnostic industry is limited. Doctors andpatients disagree on what variables should be considered when picking a lab. This study seeks to review the marketing mix ofhospitals and their applicability in the diagnostic industry. A systematic review of relevant websites, articles, periodicals, and peerreviewedjournals on google scholar, the Internet, EBSCO host, and ProQuest was done. The paper enriches the literature onmarketing characteristics of health services from a diagnostic lab perspective. This study will be helpful for professionals inlaboratory business and count on their theoretical knowledge. Moreover, this article paves the way to further research in this fieldto find an appropriate marketing mix for the diagnostic industry.